Santa Siṅgha Sekhoṃ sāhita-cintana vidhī ate vicāradhārā - Sarabajīta Kaura (Dīpaka Pabalis̱arj̱a, 2011)
Study on the works of Sant Singh Sekhon, 1908-1997, Panjabi critic
Includes bibliographical references (p. 385-400). - In Panjabi-Schr
Keywords: Sekhon; Sant Singh 1908-1997